Network pharmacology modeling identifies synergistic interaction of therapeutic and toxicological mechanisms for Tripterygium hypoglaucum Hutch - Dan Zhang (BMC Complementary Medicine and Therapies, 2021)
Abstract Background Tripterygium hypoglaucum Hutch (THH) both has prominent efficacy and unwarranted toxicity in the treatment of autoimmune diseases. Nevertheless, its pharmacological and toxicological profiles still remain to be elucidated. In the current study, the network pharmacology approach was applied to identify synergistic interaction and mechanism of efficacy and toxicity for THH from a holistic perspective. Methods The compounds from THH were collected using literature retrieval and relevant databases. After the production of putative therapeutic targets for dominant diseases and harmful targets of adverse reactions (ADRs) induced by THH, the protein-protein interactions (PPIs), topological analysis and pathway enrichment were established to distinguish the hub targets and pathways. Additionally, the binding activity of candidate ingredients with core targets were revealed by molecular docking simulation. Results A total of eight bioactive components in THH were enrolled, and 633 targets were responsible for rheumatoid arthritis (RA), 1067 targets were corresponding to systemic lupus erythematosus (SLE), 1318 targets of ADRs were obtained. The results of enrichment analysis among THH-RA, THH-SLE and THH-ADR networks indicated that pathway in cancer, hepatitis B, rheumatoid arthritis, and PI3K-Akt signaling pathway might participate in THH for treating RA and SLE. Besides, the mechanism of ADRs that induced by THH were associated with viral carcinogenesis, p53 signaling pathway, PI3K-Akt signaling pathway, and so on. Whereas, these active ingredients of THH exerted the superior binding activities with crucial targets including STAT3, VEGFA, TP53 and MMP9 that functioned synergistically efficacy and toxicity as observed via molecular docking simulation. Conclusion The present research preliminarily interpreted the synergistic interaction of therapeutic and toxicological mechanisms for THH through the comprehensive analysis of relationship and binding activity between primary components and core targets, providing a feasible and promising approach to facilitate the development of toxic and irreplaceable herbs.